UPAYA PENINGKATAN PRESTASI BELAJAR SISWA KELAS 4 SD DALAM PELAJARAN IPAS MATERI TUBUH TUMBUHAN MELALUI MODEL KOOPERATIF TIPE STAD BERBANTUAN MEDIA DIGITAL WEBSITE PORTAL ILMU PENGETAHUAN (PORITA.COM) DI SDN NGADIREJO 2 - Fathonah Nurulanbiyya; Afifah Nurul Safitri; Via Musharotul Khasanah; Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aims to improve the learning outcomes of fourthgrade students of SDN Ngadirejo 2 in the subject of Natural Sciences on the materialof the function and types of plant body parts through the STAD type cooperativelearning model assisted by the interactive website media Porita.com. This researchwas conducted in two cycles using the Kemmis and McTaggart model with thestages of planning, action, observation and reflection. The research subjects were15 students. Data collection techniques included observation, documentation, testsand interviews. The criteria for successful learning outcomes were determinedbased on the KKM value of 70. The results of the study showed that the increaseoccurred from the pre-cycle stage, cycle I and cycle II with successive presentationsfrom 54%, rising to 73% to 100%. The increase in the achievement of the KKM valueindicates that the use of the STAD model assisted by the interactive website mediaPorita.com is effective in improving the learning process and outcomes.